2016
DOI: 10.1021/acssuschemeng.6b00965
|View full text |Cite
|
Sign up to set email alerts
|

Basicity-Tuned Hydrotalcite-Supported Pd Catalysts for Aerobic Oxidation of 5-Hydroxymethyl-2-furfural under Mild Conditions

Abstract: An environmentally benign and homogeneous basefree route for 5-hydroxymethyl-2-furfural (HMF) aerobic oxidation to 2,5-furandicarboxylic acid (FDCA) in water was reported using Mg−Al−CO 3 hydrotalcite-supported Pd nanoparticles (xPd/HT-n) as catalyst. The influences of the Mg/Al molar ratio of hydrotalcite and Pd loading amount on the catalytic performance of these catalysts were originally systematically investigated. These catalysts exhibited excellent catalytic activity and FDCA selectivity in the HMF oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 59 publications
6
84
0
Order By: Relevance
“…Recently, hydrotalcite (HT; Mg 6 Al 2 CO 3 (OH) 16 .4(H 2 O)) has generated great interest in view of its potential application as support material in catalysis because of its unique advantages such as high surface area, high adsorption capacity and ion‐exchange ability. Micron sized (> 1 μm) crystalline hydrotalcite has already been used as efficient support material for guest Au, Ag, Pt, Pd and Ru nanoparticles, which have been employed as active nanocatalyst for various catalytic transformations . In addition to unique physicochemical properties of HT, the strong metal‐support interaction between guest metal nanoparticles and host HT framework provided in these studies prompted us to focus on the use of the HT matrix in the stabilization of metal nanoparticles.…”
Section: Introductionsupporting
confidence: 73%
“…Recently, hydrotalcite (HT; Mg 6 Al 2 CO 3 (OH) 16 .4(H 2 O)) has generated great interest in view of its potential application as support material in catalysis because of its unique advantages such as high surface area, high adsorption capacity and ion‐exchange ability. Micron sized (> 1 μm) crystalline hydrotalcite has already been used as efficient support material for guest Au, Ag, Pt, Pd and Ru nanoparticles, which have been employed as active nanocatalyst for various catalytic transformations . In addition to unique physicochemical properties of HT, the strong metal‐support interaction between guest metal nanoparticles and host HT framework provided in these studies prompted us to focus on the use of the HT matrix in the stabilization of metal nanoparticles.…”
Section: Introductionsupporting
confidence: 73%
“…Furthermore, Pd nanoparticles supported on Mg‐Al‐CO 3 hydrotalcite (Pd/HT) are also explored for an efficient catalytic oxidation of HMF to FDCA in water in the absence of any base additive . Recently, we explored oxidation of biomass‐derived furans (furfural and HMF) over bimetallic Ni 1− x Pd x (0.10≤ x ≤1) using air as an oxidizing agent .…”
Section: Catalytic Oxidation Of Biomass‐derived Furfural and Hmf Overmentioning
confidence: 99%
“…[197] Furthermore, Pd nanoparticles supported on Mg-Al-CO 3 hydrotalcite (Pd/HT) are also explored for an efficient catalytic oxidation of HMF to FDCA in water in the absence of any base additive. [198] Recently,w ee xplored oxidation of biomass-derived furans (furfural and HMF) over bimetallic Ni 1Àx Pd x (0.10 x 1) using air as an oxidizing agent. [200] We demonstrated that by tuningt he Ni to Pd contentsi nt he bimetallic Ni 1Àx Pd x catalyst, catalytic efficacy of Ni 1Àx Pd x catalysts towards the oxidation of furans can be controlled.…”
Section: Catalytic Oxidation Of Biomass-derived Furfural and Hmf Overmentioning
confidence: 99%
“…The main limiting factors are that the catalysts tability and processing efficiency are still not very satisfactory.M oreover,e xcess amountso fb ase additives can result in strong corrosion of equipment ands imultaneously lead to serious environmental pollution. To improve the catalytic performance of supported catalysts, numerousr esearchers have focusedo nt he study of different catalyst supports (e.g.,c arbon nanotubes, [14,21] layered double hydroxides (LDHs), [10,12,[20][21][22][23] zinc hydroxycarbonate, [19] carbon materials, [15,17,24,25] metal oxides [7-9, 20, 25] ). Commonly,astrongly alkaline aqueous medium or additional extra homogeneous base is required to achieve high yields of FDCA.…”
Section: Introductionmentioning
confidence: 99%